1998
DOI: 10.1039/a708215k
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the allomerization reaction of chlorophyll a and bacteriochlorophyll a

Abstract: A combined spectroscopic and chromatographic approach has been employed to study the products of allomerization of chlorophyll a (chl a), bacteriochlorophyll a (bchl a) and bacterioviridin (bvir) under a variety of conditions. Using high-performance liquid chromatography, mass spectrometry (MS), tandem-MS, NMR spectroscopy, UV-VIS absorption spectroscopy and protected surface-enhanced resonance Raman spectroscopy we have identified the allomers formed under all the conditions. Analysis of the different product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…(1) The enol derivatives are important in relation to the theory of electron delocalization and aromacity/antiaromacity in large macrocyclic p-systems [7]. (2) The enolate anion of Chl [8,9] [5,6,[10][11][12][13][14]. (3) It has been suggested that the enol derivatives of Chl may be involved in the primary events of photosynthetic reaction centers [15].…”
Section: Introductionmentioning
confidence: 99%
“…(1) The enol derivatives are important in relation to the theory of electron delocalization and aromacity/antiaromacity in large macrocyclic p-systems [7]. (2) The enolate anion of Chl [8,9] [5,6,[10][11][12][13][14]. (3) It has been suggested that the enol derivatives of Chl may be involved in the primary events of photosynthetic reaction centers [15].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Kuronen et al (1993) indicate a free radical mechanism. In contrast to Hynninen, however, the study of Woolley et al (1998) suggests that the hydroxyl and methoxyl radicals may not be the active species in the allomerization reaction.…”
Section: A Light-independent Allomerization Of Chlorphyllsmentioning
confidence: 76%
“…More evidence has been gathered in the last decade using HPLC coupled to MS and diode array detection (Kuronen et al, 1993;Rahmani et al, 1993;Brereton et al, 1994;Woolley et al, 1998;Gauthier-Jaques et al, 2001). The results of Rahmani et al (1993) suggest that several com peting degradation pathways are involved in allomerization.…”
Section: A Light-independent Allomerization Of Chlorphyllsmentioning
confidence: 96%
See 1 more Smart Citation
“…Several analytical studies, mostly employing modern mass spectrometric methods, were aimed at studying the allomerization reaction of Chl (Grese et al, 1990;Rahmani et al, 1993;Brereton et al, 1994;Hyvarinen et al, 1995). A thorough study by Woolley et al (1998) clearly showed that the 13 2 -CO 2 Me group is required for allomerization Scheme 4 to occur and that a double rather than single bond between C7 and C8 (e.g., Chl vs. BChl) exerts a significant influence on the reactivity of ring E: ring E in Chl a is more susceptible to oxidative ring cleavage and lactone formation than in BChl a. Mass spectrometry also played a crucial role in elucidating ring E biosynthesis for (B)Chls from different organisms (Porra and Scheer, 2000).…”
Section: Chemical Manipulations Of Ring Ementioning
confidence: 99%